Cross Section Biasing Technique in 3H(d,n)4He Reaction using the GEANT4 Toolkit - Tsormpatzoglou, Ioannis; Ziagkova, Anastasia; Kokkoris, Michael; Diakaki, Maria; Vlastou, Roza; Kaperoni, Kalliopi (HNPS Advances in Nuclear Physics, 2024)
Simulations using Monte Carlo GEANT4 [1] toolkit was performed to quantify parasitic neutrons production from the 3H(d,n)4He reaction in the TANDEM [2] accelerator laboratory at N.C.S.R "Demokritos". In this reaction, parasitic neutrons are produced, which contaminate the main neutron beam. For studying parasitic neutrons, the cross section biasing technique has been applied to increase the cross sections of the reactions and to obtain accurate statistical results in a short computational time. However, the implementation of a biasing technique can significantly impact the physical processes simulated. The experimental setup contains the accelerator line and the tritium flange, which consists of molybdenum, tritium and copper. Then, the target materials are purposefully exposed to the neutron beam to conduct cross section measurement experiments. The simulation code aims to understand neutron flux distribution and transport through the targets. Finally, the corresponding results obtained using GEANT4, through the application of biasing techniques, were compared to those resulting from the combined use of the MCNP 6.1 [3] and NeuSDesc [4] codes.